2019
DOI: 10.3892/or.2019.7002
|View full text |Cite
|
Sign up to set email alerts
|

Association of CCL2, CCR2 and CCL5 genetic polymorphisms with the development and progression of benign prostatic hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is a common chronic disease in older males. The pathogenesis of BPH remains elusive but may be associated with chronic inflammation. Chemokines and chemokine receptors have been implicated as critical mediators in the immune response and inflammatory processes. In the present study, the aim was to evaluate the association of three polymorphisms in chemokine genes, namely C-C motif chemokine ligand (CCL)2 rs1024611, CC chemokine receptor 2 (CCR2) rs1799864 and CCL5 rs2107538, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…The insertion/deletion polymorphism of the ACE gene is directly related to ACE plasma levels [ 50 ]. This variation has also previously been found to be associated with LUTS or surgery for LUTS in study populations of Mexico and India [ 43 , 45 ]. Thus, such reports prove the robustness of the current study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The insertion/deletion polymorphism of the ACE gene is directly related to ACE plasma levels [ 50 ]. This variation has also previously been found to be associated with LUTS or surgery for LUTS in study populations of Mexico and India [ 43 , 45 ]. Thus, such reports prove the robustness of the current study.…”
Section: Discussionsupporting
confidence: 60%
“…Polymorphism in several genes has been linked to the high susceptibility of BPH. For example, SNPs in CYP17, CYP19, VDR, and SRD5A2 [ 34 ] and in chemokine genes CCR2 (rs1799864) and CCL5 (rs2107538) [ 45 ] genes have been reported in BPH. Individuals with metabolic syndrome (MetS) or its individual components—including central obesity, hyperinsulinemia, insulin resistance, and dyslipidemia, are more prone to develop BPH and LUTS [ 46 – 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yoo et al (14) reported that there is a strong association between IL10 and BPH in Korean population. Furthermore, other studies have illustrated that both chronic inflammation and immune dysregulation play significant roles in the progression of BPH (15,28,29). Finally, further studies are needed to explore molecular mechanisms and signal pathways activated by estrogen in the pathogenesis of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…The interconnection between inflammation and cancer initiation is not a one-way street and there is also evidence that DNA damage can result in inflammation and thereby enhance tumorigenesis (Figure 4). One of the best examples is provided by the model of hepatocellular carcinoma induced by the carcinogen diethyl-nitrosamine, in which DNA damage contributes to necrotic cell death, resulting in an inflammatory action that activates tumor growth [19].…”
Section: Inflammation and Tumor Initiationmentioning
confidence: 99%